Technical, Anatomical, and Functional Study after Removal of a Symptomatic Cavernous Angioma Located in Deep Wernicke’s Territories with Cortico-Subcortical Awake Mapping - Silvio Sarubbo; Gianpaolo Basso; Franco Chioffi; Edward Cesnik; Beatrice Paradiso; Enrico Grandi; Enrico Fainardi; Valeria Tugnoli; Marco Farneti; Enrico Granieri (Case Reports in Neurological Medicine)
Introduction. The subcortical region underneath Wernicke’s area (WA) is a critical crossing of the eloquent language pathways involved in all semantic, phonological, syntactic, and working memory elaboration. We report the resection of a CA located underneath the dominant WA discussing the functional and anatomical evidence provided by fMRI, dissections with Klingler’s technique, and intraoperative mapping during awake surgery. Case Report. A 64-year-old right-handed female affected by daily complex focal seizures underwent f-MRI, showing language activations in the middle and inferior temporal gyri and an unusual free entry zone in the “classical” WA. The cortical intraoperative mapping partially confirmed the f-MRI results, and we approached the lesion directly through WA. Subcortical DES allowed the identification of the eloquent language pathways and the radical resection of the perilesional gliotic rim. The patient did not report deficits and she is seizures and drug free after 1-year surgery. Discussion. Cortical DES demonstrated the variability of the eloquent areas within the cortex of the dominant temporal lobe. The subcortical DES confirmed the crucial role in language elaboration and the anatomical course of the bundles underneath WA. Conclusions. Awake surgery with DES represents a reliable and dynamic technique also for safer and functional-customized resection of CAs.